2022
DOI: 10.1186/s41232-022-00239-1
|View full text |Cite
|
Sign up to set email alerts
|

Association of cellular immunity with severity of COVID-19 from the perspective of antigen-specific memory T cell responses and cross-reactivity

Abstract: Coronaviruses regularly cause outbreaks of zoonotic diseases characterized by severe pneumonia. The new coronavirus, severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has caused the global pandemic disease COVID-19 that began at the end of 2019 and spread rapidly owing to its infectious nature and rapidly progressing pneumonia. Although the infectivity of SARS-CoV-2 is high, indicated by the worldwide spread of the disease in a very short period, many individuals displayed only subclinical infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 100 publications
(169 reference statements)
0
20
0
Order By: Relevance
“…Earlier studies have indicated that a rapid and robust T cell response is critical in determining the outcome of SARS-CoV-2 infection ( 20 , 21 ). Here, we showed T cell responses as early as day 7, with peak T cell activation and proliferation at days 10 and 14 and an antigen-specific T cell response against S dominant in most infected participants.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier studies have indicated that a rapid and robust T cell response is critical in determining the outcome of SARS-CoV-2 infection ( 20 , 21 ). Here, we showed T cell responses as early as day 7, with peak T cell activation and proliferation at days 10 and 14 and an antigen-specific T cell response against S dominant in most infected participants.…”
Section: Discussionmentioning
confidence: 99%
“…While two MVA-BN doses in non-primed individuals induced low levels of poorly neutralizing antibody [17], a single dose induced robust T-cell responses [18,19], with the latter more strongly correlated with protection against severe outcomes in general (e.g. against COVID-19 disease [20]).…”
Section: (Which Was Not Certified By Peer Review)mentioning
confidence: 99%
“…Later, some of the B and T cells become memory cells that can remember past infections, thus ensuring a more efficient defense upon encountering the same pathogen a second time. The purpose of vaccination is to induce these memory cells, which are divided into following main types: antibody-producing cells, memory B cells, and memory T cells (helper and killer T cells) [ 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 ]. Antibody-producing cells are specialized cells that produce antibodies.…”
Section: Vaccination Of Sars-cov-2mentioning
confidence: 99%